Greenery for a university campus: does it affect indoor environmental quality and user well-being?. (September 2017) - Montacchini, Elena; Tedesco, Silvia; Rondinone, Tea
Abstract: In an indoor environment, greenery plays an important role for the quality of space as well as for the users' psychological well-being, comfort and health. The purpose of this study is to evaluate the feasibility of installing an indoor green wall at a university campus (Politecnico di Torino, Italy), taking into account users' perception and preferences. The paper builds on a questionnaire based survey developed in order to assess: the relationship between vertical greening systems and users' sense of well-being and comfort; the best indoor location for a green wall and its influence on the environmental quality. The paper presents the questionnaire survey results and analyses the strengths and weaknesses of vertical greenery in respondents' opinion.